Competency-Based Grammar Mastery: Teaching Parts of Speech to Freshman EFL Students - Burhanuddin; Nur, Sahril (English Language Teaching Methodology, 2025)
This study investigates the implementation of Competency-Based Education (CBE) for teaching the parts of speech to freshman EFL students in higher education. Addressing the urgent need for more effective grammar instruction, the research introduces a performance-based, learner-centered approach that links grammatical forms to authentic communication tasks. By integrating CBE principles—measurable outcomes, continuous assessment, and contextualized practice—the instruction moves beyond memorization toward demonstrable linguistic competence. Classroom observations, student outputs, and feedback reveal that CBE significantly increases learner engagement, autonomy, and mastery of basic grammatical categories. The findings highlight the novelty of applying CBE to foundational grammar, demonstrating its potential to strengthen students’ accuracy and communicative competence early in their academic journey. The study contributes a practical framework for first-year EFL instruction, emphasizing that mastery of the parts of speech is essential for students’ progression into advanced grammar and speaking performance in subsequent semesters.